Comprehensive analysis of inhibin-β A as a potential biomarker for gastrointestinal tract cancers through bioinformatics approaches - Rohit Kumar Verma; Prashant Kumar Srivastava; Ashutosh Singh (Scientific Reports)
Abstract Inhibin, β, which is also known as INHBA, encodes a protein that belongs to the Transforming Growth factor-β (TGF-β) superfamily, which plays a pivotal role in cancer. Gastrointestinal tract (GI tract) cancer refers to the cancers that develop in the colon, liver, esophagus, stomach, rectum, pancreas, and bile ducts of the digestive system. The role of INHBA in all GI tract cancers remains understudied. By utilizing GEPIA2, which uses transcriptomic data from TCGA, we examined the expression of INHBA across different GI tract cancers. The results revealed consistent upregulation of INHBA in all TCGA GI tract cancers, except for liver hepatocellular carcinoma, where it showed downregulation compared to normal tissues, along with GTEx normal samples. Significant differences in INHBA expression were noted in adenocarcinomas of the colon, pancreas, rectum, and stomach, while no such differences were observed in cholangiocarcinoma and liver cancer. Moreover, a comprehensive bioinformatics analysis has been done to demonstrate that the differences in expression levels are significantly related to pathological tumor stages and prognosis in different GI tract cancers. Mucinous adenocarcinoma, esophageal squamous cell carcinoma, and stomach adenocarcinoma show a higher frequency of INHBA alteration and are primarily linked to mutations and amplifications. DNA methylation, immune infiltration, functional enrichment analysis, the genes associated with INHBA, and survival analysis in all TCGA GI tract cancers have been extensively analyzed. In colon and stomach cancers, increased INHBA expression significantly correlates with poorer overall survival (OS). However, in colon and pancreatic adenocarcinoma, higher expression is significantly associated with worse disease-free survival (DFS). Additionally, INHBA expression exhibited a positive correlation with cancer-associated fibroblasts across all gastrointestinal (GI) tract cancers. The KEGG pathway analysis revealed that INHBA and its interacting proteins are involved in several pathways, including TGF-beta signaling, Signalling pathways regulating pluripotency of stem cells, colorectal cancer, pancreatic cancer, AGE-RAGE signaling, and so on as major pathways. These findings demonstrate that INHBA could serve as a potential biomarker therapeutic target for GI tract cancer.